2019
DOI: 10.1111/pace.13649
|View full text |Cite
|
Sign up to set email alerts
|

Comparing phase and electrographic flow mapping for persistent atrial fibrillation

Abstract: Background: An increasing number of methods are being used to map atrial fibrillation (AF), yet the sensitivity of identifying potential localized AF sources of these novel methods are unclear.Here, we report a comparison of two approaches to map AF based upon (1) electrographic flow mapping and (2) phase mapping in a multicenter registry of patients in whom ablation terminated persistent AF.Methods: Fifty-three consecutive patients with persistent AF in whom ablation terminated AF in an international multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…The index procedure was guided by clinically-indicated Focal Impulse and rotor mapping (FIRM), and EGF analysis was completed retrospectively. EGF mapping identified 40/50 (80%) of sites detected by FIRM, in agreement with other recent studies [5]. Intuitively, the authors found that sources with the highest temporal stability also had the lowest spatial variability.…”
Section: Electrographic Flow Mappingsupporting
confidence: 91%
“…The index procedure was guided by clinically-indicated Focal Impulse and rotor mapping (FIRM), and EGF analysis was completed retrospectively. EGF mapping identified 40/50 (80%) of sites detected by FIRM, in agreement with other recent studies [5]. Intuitively, the authors found that sources with the highest temporal stability also had the lowest spatial variability.…”
Section: Electrographic Flow Mappingsupporting
confidence: 91%
“…EGF mapping is a novel method of visualizing cardiac action potential flow and the details of this method have previously been published. 15 , 16 , 17 The ability to visualize action potential flow enables the identification and characterization of functional mechanisms of AF such as active sources that serve as drivers and/or triggers of AF. In many persistent AF patients, spontaneously active sources with focal or reentrant mechanisms repeatedly originate electrical excitations at defined locations in the atrial wall, which flow into the otherwise chaotic excitation waves of fibrillation.…”
Section: Methodsmentioning
confidence: 99%
“…These data show some agreement on target sites between phase mapping and other methods as electrographic flow mapping or a method that reconstructs AF signals using sinusoids in an attempt not to detect false rotational activations. [ 84 , 85 ] However, to the best of our knowledge, actual validation in experimental settings using optical mapping comparisons of the current wide range of methodologies has not been performed.…”
Section: Main Clinical Evidence Using Novel Mapping Methods For Af Ablationmentioning
confidence: 99%